PENDIDIKAN ENTERPRENEURSHIP PADA ABAD 21 (MILLENIAL) DI PONDOK PESANTREN - Ade Hasim; Amir Tengku Ramly (Universitas Ibn Khaldun Bogor, 2021)
This study aimed at investigating entrepreneurship education concept; the conduct of entrepeneurship education in 21st Century; and the effect of enterprneurship education in pesantren; and investigating the problems experienced and their solutions in 21st century. This was a case-study qualitative research. The collected data was analized qualitatively by using Miles and Huberman's interactive model. The findings of the study showed that: entrepreneurship education in pesantren aimed at preparing students (santri) to encounter real life after their graduation. Job affairs have actually been managed by Allah The Al-Mighty, yet humans should prepared themselves by sufficient skills, entrepreneurship activities in pesantren was conducted through the advanced-special program, curriculair, extra-curriculair, and non-curriculair programs, entrepeneurship activities in pesantren contributed a lot to the economic effects and the students' life skill, the coming problems in entrepeneurship activities of pesantren were caused by human resources, technology and management. To solve such problems, pesantren effortlessly tried to consolidate to the relating partners and improved their entrepeneurship management.